Steel slag-mineral slag composite micro powder
By using steel slag-slag composite powder, environmental problems caused by cement production are solved, cement substitution and solid waste resource utilization are achieved, and the performance and sustainability of concrete are improved.
Patent Information
- Application Number
- CN202411930906.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
Environmental problems caused by cement production, including resource consumption, ecological damage, high energy consumption and large carbon dioxide emissions, hinder the sustainable development of the concrete field.
Steel slag-slag composite fine powder is used as the cementitious material to replace cement. By combining steel slag fine powder, slag fine powder, phosphogypsum fine powder, slag powder and zeolite tailings powder, the unique properties of these industrial waste products are used to promote hydration reactions and improve the strength and durability of concrete.
Cement replacement has been achieved, carbon emissions have been reduced, solid industrial waste has been resourced, environmental pressure has been reduced, production costs have been reduced, and concrete application potential and performance have been improved.
Smart Images

Figure BDA0005210269480000061 
Figure BDA0005210269480000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of environmentally friendly cementitious materials, and more specifically, to a steel slag-slag composite micropowder. Background Art
[0002] As an indispensable key component of concrete, cement plays an extremely important role in the concrete system. However, the traditional production model of cement has brought many environmental problems.
[0003] Cement production is a resource-intensive industry. The mining of its main raw materials, limestone and clay, has caused huge consumption of natural resources. Limestone is the key calcium raw material for cement production. Large-scale limestone mining not only destroys the mountain topography, but also may cause a series of ecological problems, such as vegetation destruction and soil erosion. Clay, as another important raw material, also has an impact on land resources that cannot be ignored. In addition, the energy consumption in the cement production process is extremely high. From the crushing, grinding, calcination of raw materials to the grinding of finished products, each link requires a large amount of heat and electricity. What is more serious is that during the calcination of cement clinker, a large amount of carbon dioxide will be emitted. Limestone decomposes to produce calcium oxide and carbon dioxide under high-temperature calcination. This process is one of the main sources of carbon dioxide emissions in cement production. According to statistics, for every ton of cement produced, about one ton of carbon dioxide will be emitted into the atmosphere. Such a huge amount of carbon dioxide emissions makes the cement industry one of the important contributors to global greenhouse gas emissions, which has an extremely adverse impact on global climate change and aggravates the global greenhouse effect.
[0004] Since cement is the main source of carbon emissions from concrete, finding environmentally friendly materials that can replace cement has become a key task for achieving sustainable development in the concrete industry. Summary of the invention
[0005] In order to replace cement as a cementitious substance in concrete with environmentally friendly materials, thereby reducing carbon emissions, the present application provides a steel slag-slag composite micropowder.
[0006] The steel slag-slag composite micropowder provided in this application adopts the following technical solution: A steel slag-slag composite powder comprises, by weight, 30-40 parts of steel slag powder, 30-40 parts of slag powder, 5-10 parts of phosphogypsum powder, 10-20 parts of slag powder, and 5-10 parts of zeolite tailings powder, wherein the phosphogypsum is an industrial by-product.
[0007] By adopting the above technical scheme, the steel slag-slag composite micro-powder combination of the present application uses solid industrial waste products as raw materials. Steel slag and slag are the main sources of cementitious materials. The two cooperate with each other. Steel slag can provide a certain strength support in the early stage, and slag ensures the continuous growth of strength in the later stage. Phosphogypsum, as a salt activator, can stimulate the difficult-to-hydrate mineral components in steel slag and slag and promote hydration reactions. Slag promotes additional gelling reactions with its high silicon and aluminum content, improves the strength and durability of the mixed material, and zeolite tailings improves the material microstructure with its adsorption and ion exchange capacity. Through the synergistic effect of various components, the composite micro-powder has good application potential in concrete, which can not only replace cement as a cementitious material, but also realize the resource utilization of solid waste, reduce the pressure on the environment and reduce production costs.
[0008] Optionally, the steel slag powder is prepared by the following steps: The steel slag is ground after magnetic separation to control the specific surface area of the steel slag to 400-500m 2 / kg, the particle size is in the range of 1-10μm, and steel slag powder is obtained.
[0009] By adopting the above technical solution, magnetic separation treatment effectively removes metallic iron particles in steel slag, avoids rust problems in concrete, and ensures the durability of concrete. Grinding to a specific specific surface area and particle size range gives steel slag powder a larger specific surface area, increasing its chance of contact with water and other components, thereby significantly improving the hydration activity of steel slag in composite powder. In the early stage of concrete hydration, steel slag powder can react quickly to generate more cementitious products, and together with other components, it builds an early strength framework, providing strong support for the development of early strength of concrete, and its good dispersibility helps to form a uniform concrete microstructure and improve overall performance.
[0010] Optionally, the preparation method of the phosphogypsum powder is: The phosphogypsum is washed with water for multiple times until the phosphate content in the gypsum is ≤0.5% and the fluoride content is ≤0.3%; The washed phosphogypsum is calcined at 150-200°C for 2-3 hours. The calcined phosphogypsum is mixed with calcium stearate for grinding. The amount of calcium stearate added is 0.1-0.3% of the mass of the phosphogypsum. After grinding, the specific surface area is 300-400m 2 / kg of gypsum powder.
[0011] By adopting the above technical solution, the phosphate and fluoride in the phosphogypsum are removed by multiple water washings, so as to avoid excessive sulfate and fluoride interfering with the normal hydration process of cement. After calcination, the calcium sulfate dihydrate in the phosphogypsum is converted into calcium sulfate hemihydrate, and its activity is significantly improved, becoming a more effective salt activator. After being mixed and ground with calcium stearate, the calcium stearate is coated on the surface of the gypsum particles during the grinding process, which improves the dispersibility of the gypsum powder and makes it evenly distributed in the composite powder. On the other hand, it improves its selectivity in reacting with steel slag and slag, accelerates the early hydration reaction of concrete, and promotes the formation of key products of early strength such as calcium sulfonate.
[0012] Optionally, the slag powder is mixed with sodium tripolyphosphate and then ball-milled, the amount of sodium tripolyphosphate is 0.3-0.5% of the mass of the slag powder, and the particle size of the ground slag powder is 10-45 μm.
[0013] By adopting the above technical solution, when slag powder and sodium tripolyphosphate are mixed and ball-milled, sodium tripolyphosphate as a dispersant can effectively prevent slag particles from agglomerating. The obtained slag powder with a particle size in the range of 10-45μm has good filling effect and reaction activity in the composite powder system. In concrete, slag powder of this particle size can fully contact with other components, and the active silicate and other components inside it actively participate in the gelling reaction under the action of the activator, effectively filling the pores of concrete and improving the density of concrete. At the same time, it contributes significantly to the improvement of the later strength of concrete, ensuring that the concrete is structurally stable and has good performance during long-term use.
[0014] Optionally, the preparation method of the zeolite tailings powder is: The zeolite tailings are placed in a high-pressure steam environment with a pressure of 1.5-2.0MPa for 5-10 minutes, and then the zeolite tailings are soaked in a hydrochloric acid solution with a mass concentration of 5-10% for 30-60 minutes, and the acid leaching temperature is 30-50°C. After the acid leaching is completed, the zeolite tailings are mixed with polyvinyl alcohol and ground, and the amount of polyvinyl alcohol used is 0.3-0.5% of the mass of the zeolite tailings. The zeolite tailings are ground to a particle size of 10-50μm to obtain zeolite tailings powder.
[0015] By adopting the above technical solution, the zeolite tailings are treated in a high-pressure steam environment to greatly increase the porosity, make the internal active ingredients easier to expose, and the subsequent acid leaching process has a better impurity removal effect and can further increase the porosity and specific surface area. The zeolite tailings after acid leaching are mixed and ground with polyvinyl alcohol, and the polyvinyl alcohol is coated on the surface of the particles. In concrete, this treated zeolite tailings powder can give full play to its adsorption and ion exchange capacity, effectively adsorb harmful ions generated during the hydration of concrete, such as chloride ions and sulfate ions, reduce the corrosion of these ions to steel bars and the erosion of concrete structures, and protect the internal structural integrity of concrete. At the same time, its own active ingredients participate in the gelation reaction, and together with other ingredients, construct a dense microstructure, significantly improving the concrete's impermeability and freeze-thaw resistance.
[0016] Optionally, 4.5-5 parts of metakaolin are also included.
[0017] By adopting the above technical solution, metakaolin has a high volcanic ash activity and can react with calcium hydroxide, a cement hydration product, in concrete to generate more cementitious products, such as CSH gel. These cementitious products can effectively fill the internal pores of concrete, making the concrete structure more compact, thereby improving the strength of concrete, including compressive, tensile and flexural strength. At the same time, the addition of metakaolin improves the interface transition zone of concrete, making the bond between the slurry and aggregate in the concrete tighter, the microstructure more uniform, reducing stress concentration, and further enhancing the durability of concrete.
[0018] Optionally, 3-4 parts of red mud powder are also included.
[0019] By adopting the above technical solution, the red mud powder contains a large amount of aluminum oxide, which can participate in the chemical reaction in concrete to generate a new cementitious structure, thereby improving the strength of the concrete.
[0020] Optionally, 0.5-1 part of starch ether is also included.
[0021] By adopting the above technical scheme, starch ether is added to the steel slag-slag composite micropowder as a thickener to form a three-dimensional network structure in the concrete system, which can absorb a large number of water molecules, increase the viscosity of the concrete, and effectively prevent the bleeding and segregation of the concrete during the construction process, ensuring the uniform distribution of the various components of the concrete, thereby improving the stability and uniformity of the concrete.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application adopts solid industrial waste products as raw materials and is combined in specific weight proportions, wherein steel slag and slag cooperate with each other to provide early and late strength support respectively, phosphogypsum acts as a salt activator to activate the difficultly hydrated mineral components of steel slag and slag to promote hydration reaction, slag promotes additional gelling reaction with high silicon and aluminum content to improve strength and durability, zeolite tailings improves microstructure with adsorption and ion exchange capacity, and the synergistic effect of various components makes it have good application potential in concrete, which can not only replace cement as a cementitious material, but also realize the resource utilization of solid waste, thereby reducing environmental pressure and production costs.
[0023] 2. In the present application, it is preferred to wash the phosphogypsum several times until the phosphate content is ≤0.5% and the fluoride content is ≤0.3% to avoid interference with the normal hydration of cement, and then calcine at 150-200°C for 2-3h to convert calcium sulfate dihydrate into calcium sulfate hemihydrate with higher activity, and then mix and grind with 0.1-0.3% by weight of calcium stearate to obtain a specific surface area of 300-400m 2 / kg of gypsum powder, calcium stearate coated gypsum particles, not only improves the dispersibility and facilitates its uniform distribution in the composite powder, but also increases the selectivity of the reaction with steel slag and slag, accelerates the early hydration of concrete and promotes the formation of key products such as calcium aluminate.
[0024] 3. In the present application, starch ether is preferably added as a thickener to form a three-dimensional network structure in the concrete system to absorb water molecules and increase viscosity, prevent water seepage and segregation, ensure uniform distribution of various components, improve the stability and uniformity of concrete, and each additive works synergistically with the basic components to comprehensively optimize the performance of concrete. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources. Example
[0026] Example 1 A method for preparing steel slag-slag composite micropowder: The steel slag powder uses converter steel slag powder with a particle size of 1-10μm; the slag powder uses S95 grade copper slag powder with a particle size of 10-45μm; the phosphogypsum powder is an industrial by-product in the production process of wet phosphoric acid with a particle size of 3-15μm; the slag powder comes from the residue after combustion in coal-fired boilers with a particle size of 30-50μm; the zeolite tailings powder is clinoptilolite tailings powder with a particle size of 10-50μm.
[0027] Add 35 kg of steel slag powder, 35 kg of slag powder, 8 kg of phosphogypsum powder, 15 kg of slag powder and 8 kg of zeolite tailings powder into a mixer, and stir at 400 rpm for 30 minutes to obtain steel slag-slag composite powder.
[0028] Example 2 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that 30 kg of steel slag micropowder, 30 kg of slag micropowder, 5 kg of phosphogypsum micropowder, 10 kg of slag powder, and 5 kg of zeolite tailings powder are added to a mixer, and stirred at 400 rpm for 30 minutes to obtain steel slag-slag composite micropowder.
[0029] Example 3 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that 40 kg of steel slag micropowder, 40 kg of slag micropowder, 10 kg of phosphogypsum micropowder, 20 kg of slag powder, and 10 kg of zeolite tailings powder are added to a mixer, and stirred at a speed of 400 rpm for 30 minutes to obtain steel slag-slag composite micropowder.
[0030] Example 4 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that the steel slag micropowder adopts converter steel slag, and a strong magnetic field magnetic separator is used for magnetic separation. The magnetic field strength is 2 Tesla, and the converter steel slag is magnetically separated. The separated steel slag is ground using a ball mill. The ball mill is loaded with 40mm steel balls, and the ball-to-material ratio is controlled at 3:1. The speed of the ball mill is set at 30 rpm, and the particle size is detected by a laser particle size analyzer to ensure that the particle size distribution is within the range of 1-10μm; the specific surface area is measured by gas adsorption method, and the specific surface area reaches 400-500m 2 / kg stop grinding.
[0031] Example 5 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that the slag micropowder uses S95 grade copper slag powder, the copper slag powder is mixed with sodium tripolyphosphate and then ball milled, the amount of sodium tripolyphosphate is 0.4% of the mass of the slag micropowder, and the particle size of the ground slag micropowder is 10-45 μm.
[0032] Example 6 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that the phosphogypsum micropowder is gypsum, an industrial byproduct of the wet phosphoric acid production process, and the mass ratio of water to phosphogypsum is controlled at 4:1. The phosphogypsum is added to the water in the stirring tank, and the stirring speed is controlled at 200 rpm to fully disperse the phosphogypsum in the water. Stirring is continued for 15 minutes. After the stirring is completed, the stirring is stopped, and the solution is allowed to stand and settle for 30 minutes, and then the upper aqueous solution containing impurities is discharged by siphoning. Repeat the above-mentioned washing, settling, and draining steps multiple times, using new clean water each time, until the phosphate content in the gypsum is detected to be ≤0.5% and the fluoride content is ≤0.3%; The washed phosphogypsum is calcined at 180°C for 2.5 hours. The calcined phosphogypsum is mixed with calcium stearate and sent to a ball mill for grinding. The ball-to-material ratio is controlled at 3:1. The amount of calcium stearate added is 0.2% of the mass of the phosphogypsum. After grinding, the specific surface area is 300-400m 2 / kg of gypsum powder.
[0033] Example 7 A method for preparing steel slag-slag composite micropowder: the difference from Example 1 is that the zeolite tailings powder is clinoptilolite tailings powder, the zeolite tailings are placed in a high-pressure steam environment with a pressure of 1.8 MPa for 10 minutes, and then the zeolite tailings are soaked in a hydrochloric acid solution with a mass concentration of 8% for 40 minutes, the acid leaching temperature is 40°C, and after the acid leaching is completed, the zeolite tailings are mixed with polyvinyl alcohol and integrated into a ball mill for grinding, the amount of polyvinyl alcohol used is 0.4% of the mass of the zeolite tailings, and the zeolite tailings are ground to a particle size of 10-50 μm to obtain zeolite tailings powder.
[0034] Example 8 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that 4.8 kg of kaolin is also added to the steel slag-slag composite micropowder, and the kaolin is 1250 mesh kaolin powder produced by Shijiazhuang Chundi New Material Technology Co., Ltd.
[0035] Example 9 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that 3.5 kg of red mud micropowder is also added to the steel slag-slag composite micropowder, and the red mud micropowder is 325 mesh Bayer red mud micropowder.
[0036] Example 10 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that 0.8 kg of starch ether is also added to the steel slag-slag composite micropowder, and the starch ether is anionic starch ether, model 999, produced by Guangdong Hongxin Biotechnology Co., Ltd.
[0037] Comparative Example Comparative Example 1 A method for preparing steel slag-slag composite powder: The method is different from Example 1 in that no phosphogypsum powder is added.
[0038] Comparative Example 2 A method for preparing steel slag-slag composite micropowder: The difference from Example 1 is that no zeolite tailings powder is added.
[0039] Comparative Example 3 A method for preparing slag composite micropowder: The difference from Example 1 is that 70 kg of slag micropowder, 8 kg of phosphogypsum micropowder, 15 kg of slag powder, and 8 kg of zeolite tailings powder are added to a mixer, and stirred at 400 rpm for 30 minutes to obtain slag composite micropowder.
[0040] Performance testing Detection Methods 10 kg of the composite micropowders prepared in the embodiments and comparative examples were taken respectively, and cubic specimens of 150 mm * 150 mm * 150 mm were made according to the standard of water-binder ratio = 0.6, and cured for 7 days and 28 days under standard curing conditions (temperature 20 ± 2 ° C, relative humidity above 95%), and the mechanical properties were measured according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".
[0041] Take 10kg of the composite micropowder obtained in the embodiment and the comparative example, and make cylindrical test pieces with a diameter of 150mm and a height of 150mm according to the standard of water-binder ratio = 0.6. Cured for 28 days under standard curing conditions (temperature 20±2°C, relative humidity above 95%), put the cured test pieces into the test mold of the concrete impermeability tester, and seal the gap between the test piece and the test mold to prevent water from leaking from the side. Water is injected into the test mold, and the water pressure is increased by 0.1MPa every 8 hours from 0.1MPa until the test piece seeps water, and its impermeability performance is measured.
[0042] Table 1 Test data Combining Example 1 and Comparative Example 1 and Table 1, it can be seen that phosphogypsum powder has a significant effect on the strength and impermeability of the steel slag-slag composite powder. Example 1 contains phosphogypsum powder, and its 7-day compressive strength is 23.2MPa, the 28-day compressive strength is 31.5MPa, and the impermeability grade is P6; while no phosphogypsum powder is added to Comparative Example 1, the 7-day compressive strength drops to 18.2MPa, the 28-day compressive strength drops to 26.5MPa, and the impermeability grade drops to P4. This shows that phosphogypsum powder plays a role in stimulating the activity of steel slag and slag in the composite powder system, promoting the gelling reaction, thereby improving the strength and impermeability of the composite powder.
[0043] It can be seen from Example 1 and Comparative Example 2 and Table 1 that the zeolite tailings powder has a certain improvement effect on the performance of the composite micropowder. Example 1 contains zeolite tailings powder, and its 7-day and 28-day compressive strength and impermeability grade are higher than those of Comparative Example 2 (without zeolite tailings powder). This shows that the zeolite tailings powder can participate in the reaction of the composite micropowder, which may be through its properties such as adsorption and ion exchange capacity, improve the microstructure of the composite micropowder, and then enhance the strength and impermeability of the composite micropowder.
[0044] Combining Example 1 and Comparative Example 3 with Table 1, it can be seen that steel slag makes an important contribution to the strength and impermeability of the composite micropowder system. In Example 1, the ratio of steel slag micropowder to slag micropowder is reasonable, with a 7-day compressive strength of 23.2MPa, a 28-day compressive strength of 31.5MPa, and an impermeability grade of P6; while Comparative Example 3 reduces the amount of steel slag micropowder and increases the amount of slag micropowder, and the 7-day compressive strength drops to 20.8MPa, the 28-day compressive strength drops to 28.9MPa, and the impermeability grade is P4. This shows that steel slag micropowder plays a positive role in early strength development and overall performance improvement, and a reasonable ratio of steel slag to slag helps to optimize the performance of composite micropowder.
[0045] It can be seen from Examples 1-3 and Table 1 that within the scope of this application, changing the amount of each component has a relatively small effect on the performance of the composite micropowder. The amounts of the components in Examples 1-3 are different, but the 7-day compressive strength is between 22.4-23.2MPa, the 28-day compressive strength is between 30.3-31.5MPa, and the impermeability grade is P6. This shows that within the range of dosage variation of this application, the performance of the composite micropowder is relatively stable, and the synergistic effect between the components can maintain the performance of the composite micropowder to a certain extent.
[0046] It can be seen from Example 1 and Examples 4-7 and Table 1 that the treatment process of steel slag, slag, phosphogypsum and zeolite tailings powder in this application can effectively improve the performance of the composite micropowder. Compared with Example 1, the 7-day and 28-day compressive strength and impermeability grade of Examples 4-7 are significantly improved, indicating that these treatment processes can optimize the performance of the raw materials, enable them to play a better role in the composite micropowder, and improve the strength and impermeability of the composite micropowder.
[0047] Combining Example 1 and Examples 8-10 with Table 1, it can be seen that the addition of metakaolin, red mud powder and starch ether can further improve the performance of the composite powder. The 7-day and 28-day compressive strength and impermeability grade of Examples 8-10 are improved. Metakaolin generates more gelling products through its volcanic ash activity, red mud powder participates in chemical reactions to increase strength, and starch ether improves the workability of the composite powder, thereby optimizing the overall performance of the composite powder.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A steel slag-slag composite powder, characterized in that: The composition comprises 30-40 parts by weight of steel slag powder, 30-40 parts by weight of slag powder, 5-10 parts by weight of phosphogypsum powder, 10-20 parts by weight of slag powder and 5-10 parts by weight of zeolite tailings powder, wherein the phosphogypsum is an industrial by-product.
2. The steel slag-slag composite micropowder according to claim 1, characterized in that: The steel slag powder is prepared by the following steps: After magnetic separation, the steel slag is ground to control the specific surface area of the steel slag to 400-500m² / kg and the particle size to 1-10μm to obtain steel slag powder.
3. The steel slag-slag composite powder according to claim 1, characterized in that: The preparation method of the phosphogypsum powder is: The phosphogypsum is washed with water for multiple times until the phosphate content in the gypsum is ≤0.5% and the fluoride content is ≤0.3%; The washed phosphogypsum is calcined at 150-200°C for 2-3h. The calcined phosphogypsum is mixed with calcium stearate for grinding. The addition amount of calcium stearate is 0.1-0.3% of the mass of the phosphogypsum. After grinding, gypsum powder with a specific surface area of 300-400m² / kg is obtained.
4. The steel slag-slag composite micropowder according to claim 1, characterized in that: The slag powder is mixed with sodium tripolyphosphate and then ball-milled. The amount of sodium tripolyphosphate is 0.3-0.5% of the mass of the slag powder. The particle size of the ground slag powder is 10-45 μm.
5. The steel slag-slag composite micropowder according to claim 1, characterized in that: The preparation method of the zeolite tailings powder is: The zeolite tailings are placed in a high-pressure steam environment with a pressure of 1.5-2.0MPa for 5-10 minutes, and then soaked in a hydrochloric acid solution with a mass concentration of 5-10% for 30-60 minutes. The acid leaching temperature is 30-50°C. After the acid leaching is completed, the zeolite tailings are mixed with polyvinyl alcohol and ground. The amount of polyvinyl alcohol is 0.3-0.5% of the mass of the zeolite tailings. The zeolite tailings are ground to a particle size of 10-50μm to obtain zeolite tailings powder.
6. The steel slag-slag composite micropowder according to claim 1, characterized in that: It also includes 4.5-5 parts of metakaolin.
7. The steel slag-slag composite micropowder according to claim 1, characterized in that: It also includes 3-4 parts of red mud powder.
8. The steel slag-slag composite micropowder according to claim 1, characterized in that: It also includes 0.5-1 part of starch ether.
Citation Information
Cited By
Low-clinker cement fine-grained steel slag gravel pavement base material
CN120794465A
A low-clinker cement fine-grained steel slag crushed stone pavement base material
CN120794465B